A FUZZY LOGIC APPROACH IN MODELLING AND SIMULATION OF A SCHEDULING SYSTEM FOR HOSPITAL ADMISSIONS USING ARENA® SIMULATION SOFTWARE - MAT AYUS, NURUL ATIQAH (Universiti Teknologi PETRONAS, 2010)
This report basically discusses the research done and basic understanding of the chosen topic, which is on A Fuzzy Logic Approach in Modeling and Simulation of a Scheduling System for Hospital Admissions Using ARENA® simulation software. The aim of this project is to develop a simulation model of a scheduling system based on practical situation implemented on ARENA® simulation software. Besides, this project also seeks to incorporate Fuzzy Logic Control in decision making processes. This project mainly focuses to develop a model of a scheduling system for admission of hospital Emergency Department (ED) using ARENA® simulation software. It manipulates the sequence patient's flow for admissions to the hospital. The specific steps that need to be accomplished for demonstrating the technical feasibility of the model is to develop a hospital simulation model and integrate Fuzzy Logic admission control approach in ARENA® simulation software. The procedures include data gathering, model building, simulation, verification, and validation and performance analysis. Data and observation of the real process has been obtained through research at collaborated health care centre, Hospital Seri Manjung. The data is based on the backlog of patients' admission and patient flow pattern. The models depend on inputs from data collected and fitted to Visual Basic for Application (VBA) to for Fuzzy Logic Control. The output can be viewed by animation in ARENA® simulation software. The output of the simulation is generated in a form of report which summarizes all replications.